Wege zum illuminierten Buch Herstellungsbedingungen für Buchmalerei in Mittelalter und früher Neuzeit - Tif, Armand (2014)
The essays in this volume present art historical methods for research on the conditions in which books were produced and decorated in the Middle Ages and Early Modern Period. The consideration of the multiple factors impacting on the production and dissemination of illustrated books serves to improve our understanding of the works and helps to place them more accurately in the cultural discourse of their time.